Evaluation of Soil Water Assessment Tool (SWAT) Model Accuracy in Estimating Erosion and Sedimentation Rates in the Sutami Reservoir Watershed - Hendri Wijaya; Dyah Ari Wulandari; Suripin Suripin (Diponegoro University, 2025)
The storage capacity of the reservoir is affected by poor management of the Watershed (DTA), which in turn influences erosion and sedimentation levels. In 1972, the erosion rate at Sutami Reservoir was 0,18 mm/year, rising to 1.44 mm/year by 2022. This data reflects a significant increase in the erosion rate within the Sutami Reservoir watershed, highlighting the need for effective watershed management modeling. The Soil and Water Assessment Tool (SWAT) is commonly used for watershed management assessment. This study aims to predict erosion and sedimentation rates using SWAT and evaluate the accuracy of its simulations through calibration and validation. The simulation results from SWAT show that the total erosion rate is 5,280.45 tons/ha/year, with a total sedimentation of 11,662,851.94 tons/year. Additionally, These results were compared with an analysis using the USLE method, which indicated an erosion rate of 5,178.98 tons/ha/year and sedimentation of 11,060,798.14 tons/year. The comparison of both methods showed similar outcomes, suggesting that the SWAT model provides reasonably accurate predictions. The calibration process, using observed discharge data from 2022 and SWAT-simulated discharge, yielded an NSE value of 0.778, classified as 'very good.' On the other hand, validation using discharge data from 2023 and SWAT-simulated discharge yielded an NSE value of 0.660, classified as